PERUBAHAN PENGELOLAAN DAN PEMANFAATAN TANAH DESA DI KECAMATAN WATES KABUPATEN KULON PROGO PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The objective of this research is to know the types (forms) of management and use of village-owned land, the actor/party who manage and use village-owned land, the process of transferring management and use of village owned land, and the factors that cause changes in management and use of village-owned land. This research was a qualitative research adopting an explorative approach. Primary data were obtained from field observation and in-depth interview with the research objects, while the data analysis was inductive. It found four concepts, namely the government's domination, interests, degradation of village-owned land, and benefit of village-owned land. The research was concluded that the law institution produced by village-supra institution that enables the external parties to own/control village-owned land is the stimulant for the change of management and use of village-owned land. The release of village-owned land directs to a degradation of village-owned land. Leasing village-owned land adds its usage value. Village-owned land is a safety "valve" in the development of public facilities and government offices. In the past, the â¢ village government had little bargaining power in the management and